Análise da matriz curricular dos cursos de arquivologia nos componentes do ciclo de vida de dados: um estudo comparado - Madeiro, André Luiz de França (2021)
From the continuous technological advances that occurred between the end of the twentieth century and the beginning of the current century, the concern for the production, storage and access to data generated from the use of the most apparatus diverse of information technology has emerged in researchers within developed countries. These activities have required information professionals trained to work in academic and research institutions in order to ensure the validation of research and its availability to other researchers, as well as obtaining support from funding agencies to promote their activities. One of required professionals is the data archivist in order to preserve long-term data. The research proposes to analyze the classes taught in the Brazilian undergraduate programmes in Archival Studies at the Data Life Cycle for Information Science. It configures as an bibliographic, exploratory, documentary and correlational research of qualitative and quantitative nature. It was found that none of the analyzed Brazilian undergraduate programmes in Archival Studies has subjects that discuss the e-Science paradigm and the Dispose Phase of Data Life Cycle for Information Science. Although, it has been found classes can be applied at Data Life Cycle for Information Science with greater adherence at Collect, Storage and Recovery Phases of the Data Life Cycle for Information Science. Thus, it is suggests the inclusion of subjects in Brazilian undergraduate programmes in Archival Studies that address the fourth scientific paradigm and the Dispose Phase of Data Life Cycle for Information Science as way to skill the students for work as data archivist.